Character Development of Santri Through the Al-Ta'lim Al-Muta'allim Fi Thariqi Al-Ta'allum Book Study Program Al-Ausath Islamic Boarding School SMA N 1 Tegalombo Pacitan - Ismail, Ismail; Susanto, Susanto (ISTAWA, 2023)
This research examines the efforts of the Al-Austh Islamic Boarding School SMA N 1 Tegalombo Pacitan in developing the character of its students through the Al-Ta'lim Al-Muta'allim Fi Thariqi Al-Ta'allum book study program. The first aim of this research is to find out the reasons behind the establishment of the Al-Ausath Islamic Boarding School program at SMA N 1 Tegalombo Pacitan. The second is to find out how the Al-Ta'lim Al-Muta'allim Fi Thariqi Al-Ta'allum Al-Ausath Islamic Boarding School study program contributes to the development of student character at SMA N 1 Tegalombo Pacitan.Â  This research uses a qualitative approach, case study type. Data collection was carried out through observation, interviews and documentation. The main data sources in this research are the Principal, Teachers and Ustad of SMA N 1 Tegalombo Pacitan, and data analysis is carried out through condensation, presentation and drawing conclusions (verification). The results of the research show that the first background to the boarding school program at SMA N 1 Tegalombo is the importance of character education as outlined in the National Education Ministerial Regulation, which must be implemented by all educational institutions at all levels of education. Secondly, the Al-Ausath Islamic Boarding School applies the six values of the National Education Ministerial Regulation: leadership, responsibility, religion, honesty, hard work and integrity.